Combined Stresses in Plants : Physiological, Molecular, and Biochemical Aspects - Mahalingam, Ramamurthy (Springer International Publishing : Imprint: Springer, 2015)
The unique responses of plants to combined stresses have been observed at physiological, biochemical, and molecular levels. This book provides an analysis of all three levels of change in various plants in response to different combinations of stresses. The text provides a general review of the combined stress paradigm, focuses on the impact of higher CO2 levels in combination with other stresses, examines drought stress in conjunction with other abiotic factors in different crop plants as well as the combination of biotic and abiotic factors, and discusses the impact of combined stresses in forest ecosystems. Written by experts in the field, Combined Stresses in Plants: Physiological, Molecular,  and Biochemical Aspects is a valuable resource for scientists, graduate students, and post-doctoral fellows alike working in plant stresses.